Psychotherapy : A Very Short Introduction - Burns, Tom and Burns-Lundgren, Eva (Oxford, New York Oxford Univ. Press, 2015)
The rise of psychotherapy has been one of the defining features of the 20th century. In this Very Short Introduction, Tom Burns and Eva Burns-Lundgren trace the development of psychotherapy and counselling, from its origins in Freud's psychoanalysis to the variety of different approaches on offer today.
Include Index and Illustration
Keywords: Psychotherapy